Modified Lipid Particle Recognition: A Link Between Atherosclerosis and Cancer? - Amy E. Hall; Dhananjay Jade; Faheem Shaik; Shervanthi Homer-Vanniasinkam; Stephen P. Muench; Michael A. Harrison; Sreenivasan Ponnambalam (Biology)
Cardiovascular disease and cancer are major global causes of mortality. Dysfunctional lipid metabolism causes atherosclerosis, a driving force in arterial disease leading to heart attacks and strokes. In this review, we focus on emerging evidence for links between atherosclerosis and cancer. In atherosclerosis, modified and oxidized lipid particles promote plaque initiation and progression, with wider effects on cell and tissue responses. Oxidized and modified lipid particles bind to scavenger receptors (SRs) and promote intracellular signaling and pro-inflammatory responses. Increasing evidence points to SR-mediated activation and signaling promoting cancer cell growth and spread. In particular, the lectin-like oxidized low-density lipoprotein (LOX-1) scavenger receptor activates NF-κB-regulated signal transduction pathways which modulate different cellular responses. LOX-1-regulated signaling events are implicated in both atherosclerosis and cancer, depending on the cell type. LOX-1 signaling modulates cell proliferation, epithelial–mesenchymal transition, neutrophil recruitment and apoptosis. Elevated LOX-1 levels are linked to poor prognosis in arterial disease and prostate, colorectal and lung cancers. Inhibition of LOX-1 function could thus provide new therapeutic strategies for targeting both atherosclerosis and cancer.